The Oxford handbook of the economics of peace and conflict - Garfinkel, Michelle R., 1960-; Skaperdas, Stergios (New York : Oxford University Press, 2012)
This handbook brings together contributions from leading scholars who take an economic perspective to study peace and conflict. Some chapters are largely empirical, exploring the correlates and quantifying the costs of conflict. Others are more theoretical, examining the mechanisms that lead to war or are more conducive to peace.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Peace -- Economic aspects; Peace-building -- Economic aspects; War -- Economic aspects; Political violence -- Economic aspects; Conflict management -- Economic aspects